Effect of Jm-20 on Age-Related Cognitive Impairment in Mice - Wong-Guerra, M (Springer, 2025)
The decline in cognitive function associated with aging significantly impacts the well-being of elderly individuals and their families. This decline is a major recognized risk factor for neurodegenerative diseases, notably Alzheimer’s disease. Animal models of aging provide a platform for evaluating drugs concerning aspects like memory and oxidative stress. JM-20 has demonstrated protective effects on short-term memory acquisition and consolidation, along with antioxidant properties and modulation of Acetylcholinesterase activity. This study assesses the potential protective JM-20 against cognitive decline and age-related memory loss. For the study, aged mice exhibiting aging-associated damage were initially selected. Experimental groups were then formed, and the effect of 8 mg/kg of JM-20 was evaluated for 40 days on aging-related behavior, such as spatial memory, novelty recognition memory, ambulatory activity, and anxiety. Subsequently, animals were sacrificed, and the hippocampal region was extracted for redox studies and to assess acetylcholinesterase activity. Results indicated that JM-20 at 8 mg/kg reversed damage to spatial working and reference memory, exhibiting performance comparable to untreated young adult animals. Furthermore, JM-20 preserved the enzymatic activity of superoxide dismutase, catalase, and total sulfhydryl levels in age-related cognitive impairment in mice, indicating a potent protective effect against oxidative events at the brain level. However, only young, healthy animals showed decreased acetylcholinesterase enzyme activity. These findings provide preclinical pharmacological evidence supporting the neuroprotective activity of JM-20, positioning it as a promising therapeutic candidate for treating memory disorders associated with aging. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.